Hunter For A Blood Donor Application - Logadarshan, Krishnan (2022)
A blood donation is when a person gives their blood freely so that it can be taken out of their body and put into the body of someone who needs it. Blood can be donated twice a year. People are, however, less willing to donate blood nowadays. This is due to the fact that donors are required to stand in long queues to obtain an appointment to donate blood or to create an account to donate blood. Furthermore, because all registration and appointments are done on paper, there is a considerable risk of donor data being misplaced. The goal of this research is to solve a problem that arises during blood donation. We can use an application to create an account and schedule a blood donation appointment. This document also compared three different blood donations applications from different country. The Rapid Application Development (RAD) model of the Software Development Life Cycle was employed for this project (SDLC). The RAD approach divides software development into requirements planning, user design, construction and cutover. Context diagram, use case diagram, use case description, ERD diagram, data dictionary, class diagram were developed for this project. Android Studio will be used to create this project, which will be coded in Java. During the system testing phase of this project, the test cases will be executed to ensure that any potential problems in the project are detected. User Acceptance Testing (UAT) and usability testing will be performed to check that the system meets all of the project's requirements and specifications. At the conclusion of the project, the project limitations and future works also were discussed at the end.